2010
DOI: 10.1007/s12562-010-0249-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of Pacific cod populations in Korea based on microsatellite markers

Abstract: Pacific cod (Gadus macrocephalus) is a commercially important species in Korea. However, overfishing in the 1990s caused a strong decline in catch, and in response, artificially cultured juveniles have been released annually to enhance the stocks. Cod fishing has recently increased in Korea, and the variation within the cod population necessitates the study of their genetic characteristics. In this study, we utilized two newly developed and eight previously reported microsatellite markers to examine the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
(31 reference statements)
2
27
1
Order By: Relevance
“…This difference reflects the geographic isolation of the Yellow Sea genetic stock, which is not found in any other area. In contrast, Kim et al [5] found a significantly differentiated population structure between eastern and southern coast Pacific cod in Korea based on an analysis using microsatellite DNA (msDNA) markers, but no genetic differentiation between Yellow Sea and southern coast populations was reported. Grant and Ståhl [6] reported that Pacific cod experienced a severe population bottleneck in the North Pacific Ocean, which led to the loss of gene diversity and gene expression.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…This difference reflects the geographic isolation of the Yellow Sea genetic stock, which is not found in any other area. In contrast, Kim et al [5] found a significantly differentiated population structure between eastern and southern coast Pacific cod in Korea based on an analysis using microsatellite DNA (msDNA) markers, but no genetic differentiation between Yellow Sea and southern coast populations was reported. Grant and Ståhl [6] reported that Pacific cod experienced a severe population bottleneck in the North Pacific Ocean, which led to the loss of gene diversity and gene expression.…”
Section: Introductionmentioning
confidence: 90%
“…Grant and Bowen [25] suggested that either a recent population bottleneck or a founder event involving a single or a few mtDNA lineages could result in marine fish populations with both low haplotype diversity and low nucleotide diversity. A severe bottleneck event during or after the first migration of the ancestral population into the Pacific through the Bering Strait may be responsible for the low genetic variation [5]. Such a historical bottleneck would be severe around Korean coastal waters because these areas are the southern limit of the geographic range of the species.…”
Section: Genetic Diversity Of Pacific Codmentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the most important commercial species in several countries, including Korea (Kim et al 2010). Juvenile cod is a prospective recruitment, because they will return to the spawning area after growing up as their instinct in the certain season.…”
Section: Introductionmentioning
confidence: 99%